Coral Bleaching Situation and Influencing Factors in Recent Decade - Zheng, Jiamei (Transactions on Environment, Energy and Earth Sciences, 2024)
Coral bleaching is a very common but urgent problem that needs to be solved today. Coral bleaching due to global warming and other reasons is the greatest threat to the coral ecology system today. Coral reefs not only have great economic value but also have important ecological meaning. Protecting coral ecology is also one link to practicing global sustainable development. Research on bleaching events in recent years has shown that corals have different bleaching conditions under different environmental factors. Besides effects of exogenous factors such as the surrounding environment, there are also factors in coral itself, such as the different species of coral symbiotic. This is also a breakthrough in the battle againcoralsst heat bleaching events, to give hope for the coral situation. In the future, gene editing and other technology can be used to breed which have more heat-resistant or more bleaching-resistant. The current study is mainly in terms of environmental protection and strengthening coral resistance to support coral ecology. For more challenges in the future, still needs deeper research in coral heat bleaching and recovery mechanisms area and interactions between coral and symbiotic mechanisms area. Understanding the key factors influencing coral bleaching will be a prerequisite for solving the problem in the future.